2014
DOI: 10.1136/emermed-2014-203602
|View full text |Cite
|
Sign up to set email alerts
|

Decreased facial expression variability in patients with serious cardiopulmonary disease in the emergency care setting

Abstract: Background and objective The hypothesis of the present work derives from clinical experience that suggests that patients who are more ill have less facial expression variability in response to emotional cues. Methods Prospective study of diagnostic accuracy from a convenience sample of adult patients with dyspnoea and chest pain in an emergency department. Patients viewed three stimulus slides on a laptop computer that were intended to evoke a change in facial affect. The computer simultaneously video recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…With respect to the Noldus output, this device is not designed to differentiate authentic versus feigned emotions. This may explain why our prior study, which used manual facial affect coding (FACS) to analyse patients' facial expressions, did not find patients with cardiopulmonary emergencies to express more happy expressions than patients without an emergent diagnosis 8. However, only two patients in that study had PE+.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…With respect to the Noldus output, this device is not designed to differentiate authentic versus feigned emotions. This may explain why our prior study, which used manual facial affect coding (FACS) to analyse patients' facial expressions, did not find patients with cardiopulmonary emergencies to express more happy expressions than patients without an emergent diagnosis 8. However, only two patients in that study had PE+.…”
Section: Discussionmentioning
confidence: 82%
“…In daily practice, many clinicians use the phrase ‘He/she looks sick’ or ‘He/she does not look sick’ to describe their patients, yet this fundamental mode of deciding and then communicating the presence of acute illness has almost no published evidence to support its use 8. Based primarily upon experience, we believe patient affect may be one factor from the physical examination that contributes to physicians’ assessment of sickness.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Understanding how facial affect may impact the way clinicians formulate their probability estimates and make test-ordering decisions is important because sicker patients have been found to manifest different affect than those who were less sick. 25 In particular, facial expressions of disgust and anger appear to represent more serious illness. 25 Moreover, in an earlier study, we found that, among patients undergoing CTPA scanning, physician recall of patients smiling was surprisingly more common among patients with PE than among patients without PE.…”
mentioning
confidence: 99%
“…Gestalt allows clinicians to incorporate features that clinicians always use to make decisions, but may never be part of a rule. Examples might include the patient's demeanour and affect, results of recent diagnostic studies, presence of an alternative diagnosis, or patient-specific conditions such as his or her social situation, concomitant psychiatric conditions, alcohol intoxication or drug dependencies 2 3. And, its flexibility leads to gestalt's fallibility; it remains a black-box process that can change with each patient and escapes transparency that allows root cause analysis in case of failure.…”
mentioning
confidence: 99%